Effect of different farming systems on physiological response, blood parameters and endocrinological profiles in Deccani sheep - KOCHEWAD, S A; RAGHUNANDAN, T; RAO, K SARJAN; REDDY, K KONDAL; KUMARI, N NALINI; RAMANA, D B V; BALAMURGAN, T C; KANKARNE, YOGESHWAR; KUMAR, SANJEEV; MEENA, L R (The Indian Journal of Animal Sciences, 2017)
The result from revealed that T3 group have significantly (P